2018
DOI: 10.1590/s1980-220x2017022903332
|View full text |Cite
|
Sign up to set email alerts
|

Desconforto musculoesquelético, capacidade de trabalho e fadiga em profissionais da enfermagem que atuam em ambiente hospitalar

Abstract: Results demonstrated a high prevalence of musculoskeletal discomfort in the previous year and a considerable number of professionals with residual fatigue. There was a substantial portion of workers with moderate work ability and requiring attention in the medium term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
23

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
1
13
0
23
Order By: Relevance
“…In developing these activities, students can sometimes remain in the standing position for a long time. This can cause isometric muscle contractions as a result of reduced blood circulation and prolonged contraction that causes accumulation of metabolic waste in muscles and results in worsening of musculoskeletal symptoms (7,25) .…”
Section: Discussionmentioning
confidence: 99%
“…In developing these activities, students can sometimes remain in the standing position for a long time. This can cause isometric muscle contractions as a result of reduced blood circulation and prolonged contraction that causes accumulation of metabolic waste in muscles and results in worsening of musculoskeletal symptoms (7,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies are conducted on cancer patients and do not re ect occupational fatigue or work ability, they are valuable clues to show how much fatigue is related to work ability. In a study on 110 nursing professionals, 43% of the participants had residual fatigue, which was signi cantly associated with a reduction in work ability [27]. One study showed that fatigue was more frequent in unmarried workers, and they also had higher WAI scores than the other marital status workers [28].…”
Section: Discussionmentioning
confidence: 99%
“…4, No 2, febrero 2019, pp. 46-66, ISSN: 2550 -682X más en buscar atención médica; otro motivo fue que los enfermeras optan por trabajar, aun comprometidos por enfermedades (presentismo), a fin de no causar perjuicio al equipo (Silva, Araújo, Stival, Toledo, Burke, & Carregaro, 2018). Otros factores del ambiente laboral lo constituyen los psicológicos, como es la fatiga inducida por el trabajo que ha sido reconocida por su importante papel en la etiología de sobrecargas psicofísicas .Recientemente, estudios realizados han detectados fatiga en el marco de la enfermería , los que han demostrado una alta prevalencia y asociación de esa variable con condiciones deletéreas de trabajo; la fatiga representa un proceso de agotamiento físico y psíquico que modifica el estado de alerta y vigilancia, afectando las habilidades y comprometiendo el desarrollo de las actividades ocupacionales.…”
unclassified